Gaya Kepemimpinan di Lembaga Pelatihan Kerja Mandiri - Mikael Togatorop; Ana Sibarani; Novita Lastaruli Sinaga (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2021)
Leadership style includes how a person acts in the context of the organization, so the easiest way to discuss different types of leadership styles is to describe the types of organizations and situations that are produced by or suitable for a particular style. This study aims to explain the leadership style of independent LPK owners towards tailor students. The method used in this research is to use the interview method through room zoom. The data collection technique used is the question and answer instrument. The results of the analysis of the research data processing show that there is a positive and significant influence between the leadership style of the independent LPK owner on their students, the higher the motivation given by the leader, the higher the enthusiasm of students to want to exercise diligently, to improve the quality of character and character. students in everyday life. And there is also a positive and significant influence between leaders and students, the higher the influence of the leadership's affectionate attitude, the higher the learning outcomes of students, for example, the love of leaders can increase students' enthusiasm for learning in understanding the material and practices described by the leader with confidence. , as well as being active during training.